Gross primary production, respiration, and net calcification in coral reef sediments of Heron Island Lagoon, Australia, determined by in situ benthic chamber incubations - Lantz, Coulson A; Schulz, Kai Georg; Stoltenberg, Laura; Eyre, Bradley D (Supplement to: Lantz, CA et al. (2017): The short-term combined effects of temperature and organic matter enrichment on permeable coral reef carbonate sediment metabolism and dissolution. Biogeosciences, 14(23), 5377-5391, https://doi.org/10.5194/bg-14-5377-2017, 2017)
Rates of gross primary production (GPP), respiration (R), and net calcification (Gnet) in coral reef sediments are expected to change in response to global warming (and the consequent increase in sea surface temperature) and coastal eutrophication (and the subsequent increase in the concentration of organic matter (OM) being filtered by permeable coral reef carbonate sediments). To date, no studies have examined the combined effect of seawater warming and OM enrichment on coral reef carbonate sediment metabolism and dissolution. This study used 22-hour in situ benthic chamber incubations to examine the combined effect of temperature (T) and OM, in the form of coral mucus and phytodetritus, on GPP, R, and Gnet in the permeable coral reef carbonate sediments of Heron Island lagoon, Australia. Compared to control incubations, both warming (+2.4 ºC) and OM increased R and GPP. Under warmed conditions, R was enhanced to a greater extent than GPP, resulting in a shift to net heterotrophy and net dissolution. Under both phytodetritus and coral mucus treatments, GPP was enhanced to a greater extent than R, resulting in a net increase in GPP/R and Gnet. The combined effect of warming and OM enhanced R and GPP, but the net effect on GPP/R and Gnet was not significantly different from control incubations. These findings show that a shift to net heterotrophy and dissolution due to short-term increases in seawater warming may be countered by a net increase GPP/R and Gnet due to short-term increases in nutrient release from OM.